Workshop Online: Pengenalan Pariwisata Kota Palembang - Despita Despita; Marsinah Marsinah; Fitria Marisya; Dwi Hanadya; Nyayu Ully Auliana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This community service activity was carried out as a collaborative program between two tertiary institutions, STIA Satya Negara and Darussalam Polytechnic. This PKM aims to promote tourism in the city of Palembang. The activity was carried out through virtual ways (zoom meetings) with participants from Palembang city tourism activists, students and high school/vocational school students in the Palembang city area. After the pandemic, tourism in the city of Palembang entered a transitional period so that tourism, especially in this city, was getting better. Palembang is the oldest city in Indonesia which played an important role in the spread of Buddhism during the heyday of Sriwijaya so that in these traces there are many historical relics that are left behind and should be preserved as cultural heritage.